2015
DOI: 10.1001/jamaophthalmol.2015.0525
|View full text |Cite
|
Sign up to set email alerts
|

Additive Intraocular Pressure–Lowering Effects of the Rho Kinase Inhibitor Ripasudil (K-115) Combined With Timolol or Latanoprost

Abstract: for the K-115 Clinical Study Group IMPORTANCE Ripasudil hydrochloride hydrate (K-115), a novel rho kinase inhibitor, provides statistically significant intraocular pressure (IOP)-lowering effects and has a tolerable safety profile. However, no studies have evaluated ripasudil combined with β-blockers and prostaglandin analogues.OBJECTIVE To evaluate the additive IOP-lowering effects and the safety of ripasudil, 0.4%, combined with timolol, 0.5%, or latanoprost, 0.005%, in patients with primary open-angle glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 12 publications
5
93
1
1
Order By: Relevance
“…36,37 The steric affinity of the enzyme for ROCK is enhanced by the structural change in the molecule. 21 Ripasudil increases its enzyme affinity by methylation and halogenation.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The steric affinity of the enzyme for ROCK is enhanced by the structural change in the molecule. 21 Ripasudil increases its enzyme affinity by methylation and halogenation.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized trials involving 413 Japanese primary open-angle glaucoma patients found that Ripasudil achieved an average of 0.4-1.6 mmHg higher IOP reduction than the administration of timolol or latanoprost alone 15 . Phase II/III trials that aim to investigate the IOP-lowering effect of four different ROCK inhibitors (AMA0076 16 , AR-13324…”
Section: Introductionmentioning
confidence: 99%
“…15 In 2014, the first ROCK inhibitor was approved in Japan for the treatment of glaucoma. 16,17 Ripasudil shows high selectivity for ROCK inhibition, especially ROCK 2. The 50% inhibitory concentrations (IC 50 s) of K-115 for ROCK 1, ROCK 2, PKACa, PKC, and CaMKIIa were 0.051, 0.019, 2.1, 27, and 0.37 lM, respectively, while the IC 50 s of other ROCK inhibitors such as Y-27632 and fasudil were 2 to18 times higher than that of ripasudil.…”
mentioning
confidence: 99%